The Theological Potentials of Local Ecumenical Efforts in Ordinary and Everyday Life: An Ethnographic Study of South Indian Context - Swamy, Muthuraj (Ecclesial practices, 2018)
The concept and practice of ecumenism has played a crucial role in the theological construction of ecclesiology for the last few decades. In spite of the various steps taken for promoting local ecumenism in different parts of the world, the continuing challenge for ecclesiology (and also for theology in general) is to place grassroots efforts for ecumenism in the centre of theological discussions. While local ecumenism is defined and practiced in a number of ways, this essay discusses the ordinary and everyday efforts for church unity among Christians in South India, and the theological potentials of such efforts. A study of local ecumenism can contribute to the discussions in ecclesiology and ethnography, and such discussions in turn can help further to encourage local ecumenism by bringing to the centre the everyday experiences of Christians that have not often been focused or highlighted in mainline academic ecclesiology or theology.